Vitamin C enhances epigenetic modifications induced by 5-azacytidine and cell cycle arrest in the hepatocellular carcinoma cell lines HLE and Huh7 - Sajadian, Sahar Olsadat; Dooley, Steven (Clinical epigenetics, 2016)
Background: 5-Azacytidine (5-AZA), a DNA methyl transferase inhibitor, is a clinically used epigenetic drug for cancer therapy. Recently, we have shown that 5-AZA upregulates ten-eleven translocation (TET) protein expression in hepatocellular carcinoma (HCC) cells, which induce active demethylation. Vitamin C facilitates TET activity and enhances active demethylation. The aim of this study is to investigate whether vitamin C is able to enhance the effect of 5-AZA on active demethylation and to evaluate its consequence in HCC cell lines. Methods: HCC cell lines (Huh7 and HLE) were treated with 5-AZA and vitamin C. After 48 h of treatment, viability (resazurin conversion), toxicity (lactose dehydrogenase (LDH) release), and proliferation ((proliferating cell nuclear antigen (PCNA)) of single- and combined-treated cells were assessed. The effect of the treatment on 5-hydroxymethylcytosine (5hmC) intensity (immunofluorescence (IF) staining), TET, Snail, GADD45B, and P21 mRNA (real-time PCR) and protein expression (Western blot) were investigated. Results: Our results indicated that vitamin C enhances the anti-proliferative and apoptotic effect of 5-AZA in HCC cell lines. By further analyzing the events leading to cell cycle arrest, we have shown for the first time in HCC that the combination of 5-AZA and vitamin C leads to an enhanced downregulation of Snail expression, a key transcription factor governing epithelial-mesenchymal transition (EMT) process, and cell cycle arrest. Conclusions: We conclude that when combined with 5-AZA, vitamin C enhances TET activity in HCC cells, leading to induction of active demethylation. An increase in P21 expression as a consequence of downregulation of Snail accompanied by the induction of GADD45B expression is the main mechanism leading to cell cycle arrest in HCCs.
Gesehen am 23.04.2019